Graham/Hijmans/Kamp/Watkins Family Reunion at Lake Nacimiento - Watkins, Howard::::::::: (1989)
Jerry Kamp meets Robin Watkins wearing her life jacket half way and brings her back to shore Speed boat goes by on other side of the rock wall